2000
DOI: 10.2307/2656602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding population history for conservation purposes: population genetics of Saxifraga aizoides (Saxifragaceae) in the lowlands and lower mountains north of the Alps

Abstract: Several alpine species have outlying populations in the lowlands and lower mountains north of the Alps. These small, isolated populations are usually described as either (1) glacial relics, (2) descendants from populations living on forelands and moraines during the ice ages, or (3) populations founded by long-distance dispersal after glaciation. A floristic survey of the historic and present distributions and an allozyme investigation were performed on one of these relic species, Saxifraga aizoides. The speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
2
29
0
1
Order By: Relevance
“…In contrast, despite their long isolation, the overall genetic diversity of populations of S. sponhemica was similar to that found in other species with a mixed mating system (Nybom 2004). Similarly, other central European ice age relicts, such as S. paniculata (Reisch et al 2003), and S. aizoides (Lutz et al 2000), that occur on rocks have also maintained high genetic diversity despite a fragmented distribution. The maintenance of genetic diversity of these plants is probably due to their longevity and the long-term stability of their habitats (Young et al 1996;Tang et al 2010).…”
Section: Genetic Diversity Within Populationsmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, despite their long isolation, the overall genetic diversity of populations of S. sponhemica was similar to that found in other species with a mixed mating system (Nybom 2004). Similarly, other central European ice age relicts, such as S. paniculata (Reisch et al 2003), and S. aizoides (Lutz et al 2000), that occur on rocks have also maintained high genetic diversity despite a fragmented distribution. The maintenance of genetic diversity of these plants is probably due to their longevity and the long-term stability of their habitats (Young et al 1996;Tang et al 2010).…”
Section: Genetic Diversity Within Populationsmentioning
confidence: 72%
“…Strong genetic differentiation has been reported for isolated alpine relict populations, such as Saxifraga cernua (Bauert et al 1998), Erinus alpinus (Stehlik et al 2002) and for the lowland remnant populations of Saxifraga paniculata (Reisch et al 2003). However, not all studies have found low genetic diversity in ice age relicts (Lutz et al 2000;Reisch et al 2003), presumably due to the longevity of the species buffering random genetic drift. Genetic variation has profound implications for species conservation (Schaal et al 1991;Ellstrand and Elam 1993;Ouborg et al 2006) and assessing genetic variation within and between populations is essential for efficient conservation measures for rare species.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario has been recently confirmed by phylogeographic work (Tremetsberger et al 2002;Parisod and Besnard 2007). In accordance, Reisch et al (2003) found some evidence in favour of the glacial relict hypothesis for lowland stations of Saxifraga paniculata in Germany, but no corresponding evidence was detected for Sesleria albicans in Germany (Reisch et al 2002) or Saxifraga aizoides in the Swiss Canton of Zürich (Lutz et al 2000). For the especially scattered and small populations of Asplenium septentrionale mainly occurring on erratic rocks in the Swiss lowlands and being one of the historically most prominent examples of a glacial relict species (p. 1165), Holderegger and Schneller (1994) showed that the present lowland stations are rather the result of long-distance dispersal of spores than being glacial remnants.…”
Section: Glacial Survival Outside Of Glaciated Regions: Glacial Relictsmentioning
confidence: 70%
“…Combinada esta circunstancia con la estructura insular de cumbres y valles, semejantes a archipiélagos entre cuyos elementos es difícíl un intercambio que suavice los vaivenes genéticos, ello resulta en una rápida multiplicación de los endemismos. En efecto, las montañas en general, y los niveles subalpino, alpino y sus homólogos en particular, son especialmente ricos en especies endémicas (LUTZ et al, 2000).…”
Section: Las Montañas Como Refugiosunclassified